Pembelajaran Seni Kriya Topeng Sebagai Upaya Pembentukan Karakter Kreatif Siswa Kelas XI IPA 1 SMA N 5 Tegal - FAIZ, AFFAN (Universitas Negeri Semarang, 2015)
The research problems are include (1) How is the educational value of creative character that is reflected in the learning mask craft art class XI IPA 1 SMAN 5 Tegal? (2) How does the character creation mask is displayed class XI IPA 1 SMAN 5 Tegal? The aim of this study were. Data obtained from observation by the pilot implementation of the action, direct observation, interviews, documentation and photo archives. Overall mask craft art learning takes place quite smoothly. In the evaluation of the work, the average value obtained by the students of class XI IPA 1 is 78.4 which is classified in either category. Based on the observation and analysis of research, some of the students' work that still does not meet the aesthetic value. That is because the students make a mask with no regard to the value of beauty. Creative character in learning the art of craft mask Class XI Science 1 can appear as well as integrated in the student activities during work and organize.